1988
DOI: 10.1038/333850a0
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory properties of LFA-1 α and β chains in human T-lymphocyte activation

Abstract: Lymphocyte function-associated antigen-1 (LFA-1) is a heterodimer composed of an alpha and beta chain that is expressed on the surface of most leukocytes and is an essential molecule for adhesion reactions between cells participating in the immune response. A putative ligand for LFA-1 is the intercellular adhesion molecule ICAM-1 (refs 3-5). Leukocyte adhesion abnormality is found in patients with LFA-1 deficiency. It is not clear whether binding of ligand to the LFA-1 molecule merely spatially orientates cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
79
3

Year Published

1990
1990
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(87 citation statements)
references
References 25 publications
5
79
3
Order By: Relevance
“…15,34,35 As mentioned previously, Mac-1 activity interferes with LFA-1 mediated aggregation 30 and it has been proposed that dysregulated adhesion and formation of immunological synapse caused by Mac-1 activity might explain down-regulated T-cell activation. 15 In this regard, it has been proposed that via constitutively active Mac-1 on macrophages, in contrast to functionally inactive Mac-1 on dendritic cells, antigen presentation in vivo is restricted to dendritic cells.…”
Section: Discussionmentioning
confidence: 89%
“…15,34,35 As mentioned previously, Mac-1 activity interferes with LFA-1 mediated aggregation 30 and it has been proposed that dysregulated adhesion and formation of immunological synapse caused by Mac-1 activity might explain down-regulated T-cell activation. 15 In this regard, it has been proposed that via constitutively active Mac-1 on macrophages, in contrast to functionally inactive Mac-1 on dendritic cells, antigen presentation in vivo is restricted to dendritic cells.…”
Section: Discussionmentioning
confidence: 89%
“…There are several possible explanations for the inhibitory effects of this mAb. In some studies, mAbs to the 02 subunit of leuko-1533 cyte integrins have been shown to transduce negative regulatory signals to T cells (van Noesel et al ., 1988) and a similar mechanism might be operative for mAb 24 . Alternatively, mAb 24 might be cytotoxic for functioning cells .…”
Section: Mab 24 Does Not Block Leukocyte Integrin Binding To Ligandmentioning
confidence: 99%
“…One explanation might be that mAb 24 induces intracellular signals, enabling LFA-1 to combine with ligand with increased avidity. Such activity has been suggested for other LFA-1 a subunit mAbs that enhance proliferation, rather than inhibit function (van Noesel, 1988;Carrera et al ., 1988;Wacholtz et al . 1989;Pardi et al ., 1989).…”
Section: Mab 24 Does Not Block Leukocyte Integrin Binding To Ligandmentioning
confidence: 99%
“…This adhesion of monocytic cells is mediated by the LFA-1 and ICAM-1 molecules [10,11]. Since binding of ligand to LFA-1 is required for T cell function [12] and the existence of regulatory signals conveyed by LFA-1 has been suggested for T lymphocytes [13,14], we have analyzed in this report the possible occurrence of cell differentiation in the human promonocytic U-937 cells when these cells are induced to agregate via LFA-1/IC A M -l by a mAb specific for LFA-1.…”
Section: Introductionmentioning
confidence: 99%